The Illustrations of Michael Glycas’ Βίβλος χρονική in the Marcianus gr. 402 - Lovino, Francesco (Actual Problems of Theory and History of Art, 2013)
In the 13th c. the Greek communities tried to resist to the process of latinization started by the Anjou kingdom in Salento. Th is sort of ethnic resistance generates a cultural renaissance especially concerned with manuscripts production. Th e article examines one of these codices, the Marcianus gr. 402, in relationship with the particular milieu where it was copied and illustrated.
Keywords: Byzantine illumination; Michael Glycas; 13th century; Anjou Kingdom; Salento; Mark of Otranto; Marciana Library